Sufism Between Asceticism and Jihad: A Conceptual and Historical Review - Suratman , Junizar; Fatarib , Husnul; Saharuddin , Desmadi (LPPPM STAI Darul Hikmah Bangkalan, 2021)
In the picture of ordinary people, Sufism teaches Zuhud and distances itself from the world in theory and practice. But this is different from reality. Sufism orders in the archipelago also appeared in the vanguard to fight and repel the invaders. The history of Islamic civilization records a series of resistance movements led by Sheikh Sufism with his followers to fight against the Dutch colonialists. For this to become evident to us, we must examine some of their words and actions: Abu Hamid Al-Ghazali wrote his book (Reviving the Sciences of Religion) during the period of the Crusaders victory over the Levant, and the author remembered everything from the works of hearts and did not remember to write a chapter on jihad. We conducted literature studies and verified and interpreted the descriptions in the literature. With a descriptive analysis, the approach is obtained. The conceptual ambiguity that afflicted Sufism regarding the concepts of jihad and the application of Islamic law